Indeks Subjek Volume 28, Tahun 2008 - Indeks Subjek Volume 28, Tahun 2008 (agriTECH, 2008)
Acceptability 34Acetic acid bacteria 70Adsorption system 137Aflatoxin B1 146, 157, 162Aflatoxin B1, B2, G1, G2 109Andaliman extract 102Antioxidant activity 91Apple 70, 84Area 113Asset management 130Aspergillus oryzae 146Bamboo 76Banana cv Mas 15Base lubricant 120Binding agent 22Biocontrol agents 84Biogas 58BOD 58Boiling 162Bumbu pecel 157Butyrate arrowroot starch 63Butyrulization 63Calcium fortified-rice 34Calcium gluconateCalcium lactate 34Carrot extract effervescent powder 150Catechin 174Cellulose 76Chemical component 76Chilling Injury 15Chitosan 167Cider fermentation 70Citric acid 150Coating 167COD 58COLE value 1Corn 28